Contact with nature and its relationship with vitality and negative affect in surfing athletes: the mediating role of basic psychological needs - Martínez, Bruno (2023)
The scientific literature consistently demonstrates the benefits for physical and mental health obtained from activities in natural environments instead of urban ones. Such is the case of surfing, a sport practiced in contact with nature. This study uses the psychological needs theory from self-determination theory (Ryan & Deci, 2017) to explain why surfing is so beneficial. This study investigated the relationship between contact with nature, basic psychological needs (satisfaction and frustration), vitality, and negative affect in 236 amateur athletes of various surfing modalities (bodyboard, longboard, surfing, paddleboard, and bodysurf). The examination of the psychometric properties of the instruments showed adequate evidence of validity and reliability. Results from path analysis showed that contact with nature was associated with greater vitality and lower negative affect —the satisfaction of the basic psychological needs mediated these associations—. The article discusses these results regarding self-determination theory and its relationship with well-being and vitality.